Pengaruh Online Destination Brand Experience Terhadap Minat Berkunjung Wisatawan Dengan Online Destination Brand Credibility Sebagai Variabel Mediasi di Kota Denpasar - Dewi, Ni Kadek Vira Kumara; Sudiksa, I Nyoman; Kalpikawati, Ida Ayu; Pinaria, Ni Wayan Chintia (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
This research aims to analyze the effect of online destination brand experience on tourists' interest in visiting with online destination brand credibility as a mediating variable in Denpasar city. The questionnaire was used as a data collection method and distributed to 100 respondents. The data analysis techniques used are classical assumption tests (normality tests, multicollinearity tests, and heteroskedasticity tests), path analysis, determination coefficient tests, and Sobel tests. The results showed that: 1) the online destination brand experience (ODBE)’s variable has a positive and significant effect on visiting interest, 2) the ODBE’s variable has a positive and significant effect on the online destination brand credibility (ODBC)’s variable, 3) the ODBC’s variable has a positive and significant effect on visiting interest, and 4) the ODBE’s variable has a positive and significant effect on the interest in visiting with the ODBC’s variable as a mediation variable. The Tourism Office of Denpasar City should make various efforts to shape the tourist experience online to increase the interest of domestic tourist through uploads on the Denpasar Instagram account related to tourist attractions in Denpasar